Single minute exchange of dies with fuzzy-analytic hierarchy process method for setup time reduction : an application in advanced composite manufacturing industry / Mohd Syazwan Faiz bin Soberi. - Mohd Syazwan Faiz Soberi (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2017)
This section explained the objectives of the research study. The purpose is to give the view of what this research is all about and to make it clear what is need to be achieved at the end of this research study. This research aims at the following objectives ; to develop SMED-FAHP methodology for solving setup time reduction problem ; to validate the developed methodology by using case studies from advanced composite manufacturing industry ; to implement the best improvement solutions suggested by the developed methodology.